Psoas Abscess: Evaluation of 15 Cases and Review of the Literature - Hüseyin Tarhan; Özgür Çakmak; Hakan Türk; Ertan Can; Sıtkı Un; Ferruh Zorlu (Journal of Urological Surgery)
Objective Psoas abscess (PA) is a rare disease, presentingwith high mortality and morbidity particularly when diagnosed late. We aimed to evaluate thepatients with PA in terms of etiological factors and treatment results. Materials and Methods Data of 15 patients diagnosed with PA between June 2008 and June 2014 were retrospectively analyzed. Patients who were diagnosed with PA by ultrasonography (US) and/or computed tomography (CT), and had all the relevant data available were included in the study. Results Among fifteen patients diagnosed with PA, 6 (40%) were women and 9 (60%) were men, and the mean age was 58.5 years (range, 41-75 years). All psoas abscesses were unilateral, and the right side was affected in 12 (80%), and the left in 3 (20%) cases. The average size of the abscesses was 8 cm (range, 4-30 cm). Five cases (33.3%) had a primary, and 10 (66.7%) had a secondary psoas abscess. All patients were given broad-spectrum antibiotics. Two cases (13.3%) were treated with percutaneous drainage and antibiotics while 13 (86.7%) patients underwent open surgical drainage and antibiotic therapy. Conclusion Psoas abscess is a rare disease, with non-specific clinical signs resulting in difficulty in diagnosis. However, early diagnosis and treatment may provide a high cure rate. PA should be considered in patients who had history of abdominal surgery and high fever resistant to treatment.